PENGARUH METODE SIMULASI TANGGAP BENCANA ALAM TERHADAP KEMAMPUAN MITIGASI PADA ANAK TUNAGRAHITA RINGAN DI KELAS C/D VI SLB PERWARI PADANG - Suci - Rinanda (Universitas Negeri Padang, 2013)
This research of background by problems faced by student of intelegance Below class C/VI in SLB Perwari Padang, that is ability of a child mitigasi on the happening of earthquake very minim once. Though earthquake can come any time and endanger child x'self. To overcome the the problems require to look for by its way out, so that a child can do mitigasi in class on the happening of unassisted earthquake of others. Hence done at research which in form of experiment to know ability of a child mitigasi on the happening of earthquake. Research type the used is Quasi Experiment, design pretest-postest group one that is executed experiment at one group with out using comparator group. This Research Subjek is four student people of intelegance below of class C/D VI in SLB Perwari Padang. Data obtained by using deed tes. Data analysis the used is test of U Mann-Whitney with criterion examination of hypothesis accepted by if Uhit > Utab and outside condition of hypothesis in refusing at level of signifikan 95% or = 0,05. Result of data processing show Uhit = 2 and Utab = 0, its meaning of hypothesis accepted. Become result of research indicate that Method Simulation Listen Carefully Natural Disaster Have an Effect on to Ability of Mitigasi aChild of intelegance below of class C/D VI in SLB Perwari Padang. For that suggested on the side of school to be always give education help ownself at child in the case of mitigasi in class on the happening of earthquake and at the time of happened child earthquake can help unassisted their self of others.